Morphological Effect of Green Synthesis Cerium Oxide Nanoparticles Enhanced Antibacterial Activity - Gusliani Eka Putri; Putri Dafriani; Ika Yulia Darma; Sri Handayani; Widyastuti; Nor Monica Ahmad; Arniati Labanni; Syukri Arief (ASEAN Journal of Chemical Engineering, 2025)
Cerium oxide nanoparticles (CeO₂NPs) were successfully synthesized using two methods, which are the precipitation and green synthesis. In the green synthesis approach, leaf extracts from Moringa oleifera and Uncaria gambir Roxb. acted as a natural capping and reducing agents. In contrast, ammonium hydroxide was used in the chemical precipitation method. X-ray diffraction (XRD) analysis confirmed the formation of CeO₂NPs with a cubic fluorite structure. Scanning electron microscopy (SEM) revealed that the nanoparticles had an agglomerate morphology. In contrast, transmission electron microscopy (TEM) showed that the CeO₂NPs were predominantly spherical, with average particle sizes of approximately 5-20 nm for the green synthesis method and 10-40 nm for the precipitation method. The antibacterial assays demonstrated significant activity, particularly against Staphylococcus aureus, with the inhibition zones measuring up to 11.05 mm. These findings suggest that green-synthesized CeO₂NPs hold promising potential for applications in the biomedical field due to their biocompatibility and antibacterial properties.